The interaction between corporate social responsibility and value added intellectual capital: Empirical evidence from Turkey - AYBARS, ASLI (My University, 2011)
Purpose - Corporate social responsibility (CSR) has become one of the mainstream issues for sustainable corporate performance in recent decades. Engagement in CSR activities has proven to have certain benefits for companies, ranging from better financial performance to shareholder wealth maximisation. Companies' value creation process has been dominated by companies' hidden assets and concurrently the concept of value added intellectual capital (VAIC). The purpose of this study is to provide evidence from an emerging market about the interaction between CSR and VAIC, and thus contribute to the understanding and awareness of the significance of socially responsible investments for companies. Design/methodology/approach - The empirical analyses, which take into account VAIC and its dimensions, are conducted on a sample of manufacturing companies listed on the Istanbul Stock Exchange (ISE) during the period 2007-2008. It is shown that some causality is related to the existence of a lag during the periods for the variables CSR and VAIC. Based on previous empirical studies, this study conducts the analyses based on the assumption that there may be a relationship between firm age, financial leverage, return on sales and market-to-book ratio and CSR. Findings - The results fail to provide any significant relationship between CSR and VAIC during the period analysed. These findings should not overshadow the benefits of CSR, but should be attributed to the time it takes for these investments to have an impact on firms' intellectual capital. Practical implications - A larger sample of firms covering a longer time span could be utilised. Generation of a CSR index in Turkey that eliminates the subjectivity of CSR measurement will undoubtedly improve the accuracy of the analyses. Originality/value - This paper increases the understanding of the relationship between corporate social responsibility and value-added intellectual capital. This research is also the first research to have examined Turkish companies for CSR and VAIC issues. Copyright © 2011 Emerald Group Publishing Limited. All rights reserved.
Keywords: Corporate social responsibility; Emerging markets; Turkey; Value added intellectual capital